The Relationship Between Knowledge Level about Anemia and Hemoglobin Levels in Adolescent Girls - Icha Aulya Praditaningrum; Winarsih Nur Ambarwati (Jurnal Keperawatan Profesional, 2026)
Anemia remains a common health problem worldwide, especially among adolescent girls. According to data from the World Health Organization, the prevalence of anemia in women of childbearing age reaches 29.9%, reflecting the high rate of anemia among adolescent girls. This condition can affect concentration at school, productivity, and increase the risk of reproductive health problems in the future. This study aims to explore the relationship between the level of knowledge about anemia and hemoglobin levels in adolescent girls. This study uses a quantitative design with a cross-sectional approach, involving 36 female students aged 15-17 years who were selected based on respondent availability. The level of knowledge was measured using a questionnaire with 21 questions that had been tested for validity and reliability, with a Cronbach's alpha value of 0.834. Hemoglobin levels were examined using the cyanmethemoglobin method. The results showed that the majority of respondents had good knowledge (88.9%), while 52.8% were anemic. The chi-square test showed no significant relationship between knowledge level and hemoglobin levels (p=0.542). These findings indicate that good knowledge does not always guarantee normal hemoglobin levels, as other factors such as diet and adherence to iron supplementation also play an important role. Appropriate health measures are needed, including a balanced diet and support for health education programs.